‘The value of civility?’. - Boyd, Richard (Urban Studies (Routledge), 2006)
This essay argues for civility's vital place in contemporary urban life. Contrary to many critics who see civility as a conservative or nostalgic virtue deployed to repress difference and frustrate social change, it is argued that civility should be understood as democratic, pluralistic and premised on a sense of moral equality. Civility's most obvious contribution is functional—in easing social conflicts and facilitating social interactions in a complex and diverse market society. However, there is also and maybe more importantly an intrinsic moral value to civility. Observing the formal conditions of civility is one of the ways in which we communicate respect for others and generate habits of moral equality in the everyday life of a democracy.